Race and sex differences in pain sensitivity and beliefs - Bagwath Persad, Leeana Aarthi (My University, 2015)
Differences in pain perception and beliefs have been demonstrated between races and sexes. Beliefs, social influence, psychological factors, and socioeconomic status have been attributed to these differences in pain. There currently are no data on whether sex and racial differences in pain perception and beliefs exist in the South African population. Therefore in this study I evaluated sex and racial differences in pain perception and pain beliefs within a cohort of black and white Southern African university students. Sixty-four black and 56 white female students and 44 black and 52 white male students were recruited from the University of Witwatersrand. Cold pain tolerance was assessed using the cold pressor test, and pressure-pain was assessed using a blunt pressure algometer. Pain intensity was measured after both pain tests and pain tolerance was recorded. Psychological variables and socioeconomic status were evaluated using the Pain Catastrophizing Scale; Hopkins Symptoms Checklist-25; Appropriate Pain Behaviour Questionnaire and the Assessment of Socioeconomic Status questionnaire. Univariate analyses were carried out for all variables, for the comparison of black males against black females; white males against white females; white females against black females, and white males against black males. Regression tree analyses were used to determine the correlates of experimental pain tolerance, pain intensity and pain beliefs, to the variables. Black males and females had a lower tolerance to cold pain (p = 0.01; p < 0.01) compared to white males and females, as well as greater depression (p < 0.01; p = 0.02) and pain catastrophizing (p = 0.03; p < 0.01). In general, females had a lower tolerance to pressure pain (p < 0.01; p < 0.01), as well as greater anxiety (p < 0.01; p < 0.01), depression (p < 0.01; p < 0.01), and pain catastrophizing in black females (p < 0.01). There were no differences in rating of pain intensity for the cold or pressure pain stimuli between the sexes and races, except for black females, who reported greater pain intensity during the cold pain test (p < 0.01). Males and females were more accepting of females expressing pain than men (p < 0.01; p = 0.04). In particular, black males felt men should not express pain (p < 0.01). Regression analyses revealed that pain beliefs on men; pain tolerance; and cold pain intensity were correlated with race and sex difference. In conclusion, pain tolerance and sensitivity to experimental pain were affected by both race and sex in this cohort of black and white South African students. Whilst these data need to be verified in patient cohorts, they have important implications for the assessment and management of pain in South Africa.
A Dissertation submitted to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, in fulfillment for the degree of Master of Science in Medicine. Johannesburg, 2014
Keywords: Pain